Professional development and teachers' training: Analysis of some European educational reports - Stefania Nirchi (Pensa MultiMedia, 2022)
The development of the teachers' expertise and competences is a strategic dimension for schools, in terms of equity and quality. However, to take on this challenge there is an urgent need to invest in continuous teachers' training, in order to acquire those key competences required at European level. Starting from these elements, the paper reflects on the main dimensions of teachers' continuing professional development by comparing the Eurydice's Teachers in Europe: Careers, Development and Well-being report's data, with those on teachers' practices and perceptions emerging from the Teaching and Learning International Survey (TALIS) by OECD.